Trigonometry Formulas



sin2θ + cos2θ = 1

1 + tan2θ =  sec2θ

1 + cot2θ = cosec2θ


sin (A+B) = sinA.cosB + cosB.sinA

sin (A-B) = sinA.cosB - cosB.sinA

cos (A+B) = cosA.cos(-B) + sinA.sin(-B)

cos (A-B) = cosA.cosB + sinA.sinB


sin(-θ) = -sin θ

sin(90°- θ) = +cos θ

sin(90°+θ) = +cos θ

cos(-θ) = +cos θ

cos(90°- θ) = +sin θ

cos(90°+θ) = -sin θ

tan(-θ) = -tan θ

tan(90°- θ) = +cot θ

tan(90°+θ) = -cot θ

cot(-θ) = -cot θ

cot(90°- θ) = +tan θ

cot(90°+θ) = -tan θ

sec(-θ) = +sec θ

sec(90°- θ) = +cosec θ

sec(90°+θ) = -cosec θ

cosec(-θ) = -cosec θ

cosec(90°- θ) = +sec θ

cosec(90°+ θ) = +sec θ



sin(180°- θ) = +sin θ

sin(180°+θ) = -sin θ

cos(180°- θ) = -cos θ

cos(180°+θ) = -cos θ

tan(180°- θ) = -tan θ

tan(180°+θ) = +tan θ

cot(180°- θ) = -cot θ

cot(180°+θ) = -cot θ

sec(180°- θ) = -sec θ

sec(180°+θ) = -sec θ

cosec(180°- θ) = +cosec θ

cosec(180°+ θ) = -cosec θ





sin 2θ = 2sinθcosθ

= 2tanθ /(1+tan2θ)

cos 2θ = cos2θ-sin2θ   
        = 2cos2θ-1
       = 1-2sin2θ
       = (1-tan2θ)/(1+tan2θ)

tan2θ= 2tanθ/(1-tan2θ)

sin3θ = -sin3θ + 3cos2θsinθ
         = -4sin3θ + 3sinθ

cos3θ = cos3θ - 3sin2θcosθ
           = 4cos3θ - 3cosθ

tan3θ = (3tanθ-tan3θ)/(1-3tan2θ)



tan(A + B) =

sin(A + B)

=

sinA.cosB + cosA.sinB

cos(A + B)

cosA.cosB - sinA.sinB



Some Appreciation Please!




  Posted on Tuesday, March 3rd, 2015 at 11:30 AM under   Trigonometry